Visual brand communication toward brand content / Muhamad Hanapi Khamis ... [et al.] - Khamis, Muhamad Hanapi; Mohd Azni, Zuliani; Abdullah, Muhammad Hakimi Tew; Abd Aziz, Siti Hajar (2021)
The surge of communication technology has induced the way people live. The consumers are moving towards social media that makes each brand adapts the way they position by succeeding consumers to social media. To establish the engagement toward brand content, the brand needs to stand out by making it vital to understand the kind of visual preferences their target customer needs. This article will align a collection of research that focuses in establishing visual brand communication for brand content